2007
DOI: 10.1100/tsw.2007.230
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Induced Glial Activation: Mechanisms of Activation and Implications for Opioid Analgesia, Dependence, and Reward

Abstract: This review will introduce the concept of toll-like receptor (TLR)–mediated glial activation as central to all of the following: neuropathic pain, compromised acute opioid analgesia, and unwanted opioid side effects (tolerance, dependence, and reward). Attenuation of glial activation has previously been demonstrated both to alleviate exaggerated pain states induced by experimental pain models and to reduce the development of opioid tolerance. Here we demonstrate that selective acute antagonism of TLR4 results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
286
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(298 citation statements)
references
References 54 publications
11
286
0
1
Order By: Relevance
“…A recent report showed spinal TLR4 antagonism during sciatic nerve damage that leads to neuropathic pain in rats potently alleviated pathological pain (Hutchinson et al, 2007). In addition, this study was the first to demonstrate that, like neuropathic pain, opioids activate glia via TLR4 activation that leads to opioid-induced tolerance (Hutchinson et al, 2007). These findings have profound implications on future treatment strategies for clinically utilized opioids, as TLR activation appears to play a significant role in neuropathic pain.…”
Section: Toll-like Receptor Signaling In Chemokine-mediated Pathologimentioning
confidence: 58%
See 1 more Smart Citation
“…A recent report showed spinal TLR4 antagonism during sciatic nerve damage that leads to neuropathic pain in rats potently alleviated pathological pain (Hutchinson et al, 2007). In addition, this study was the first to demonstrate that, like neuropathic pain, opioids activate glia via TLR4 activation that leads to opioid-induced tolerance (Hutchinson et al, 2007). These findings have profound implications on future treatment strategies for clinically utilized opioids, as TLR activation appears to play a significant role in neuropathic pain.…”
Section: Toll-like Receptor Signaling In Chemokine-mediated Pathologimentioning
confidence: 58%
“…Further, blocking spinal cord TLR4 production in neuropathic rats also blocked pathological pain and microglial/macrophage activation (Tanga et al, 2005), supporting that TLR4 signaling in the spinal cord is important for mediating neuropathic pain. A recent report showed spinal TLR4 antagonism during sciatic nerve damage that leads to neuropathic pain in rats potently alleviated pathological pain (Hutchinson et al, 2007). In addition, this study was the first to demonstrate that, like neuropathic pain, opioids activate glia via TLR4 activation that leads to opioid-induced tolerance (Hutchinson et al, 2007).…”
Section: Toll-like Receptor Signaling In Chemokine-mediated Pathologimentioning
confidence: 64%
“…Previous studies have shown that opioid receptors are [3,32,33] . After chronic or acute exposure to morphine, activated neurons and glia exhibit increased expression of pro-infl ammatory cytokines, such as TNF-α, IL-1β, IL-6 [19,34,35] , and chemokines [36,37] .…”
Section: Discussionmentioning
confidence: 98%
“…118 This dual activity at both neuronal and glial cells is common with other clinically relevant opioids. 115 It has recently been demonstrated that morphine-3-glucuronide has TLR-4 agonist activity, indicating that codeine and morphine metabolites may contribute to this action. 119 For a detailed discussion regarding the role of TLR-4 in opioid-induced glial activation see review by Watkins at al.…”
Section: Opioid-induced Glial Activationmentioning
confidence: 99%
“…107 Pre-clinically opioid-induced glial activation is known to oppose opioid analgesia and enhance opioid adverse effects including tolerance, dependence, reward and respiratory depression. 115,116 Interestingly, opioid-induced glial activation is mediated through activation of TLR-4, exposing the potential to separate the beneficial actions of opioids from their unwanted adverse effects. 92 Pre-clinical studies have demonstrated that while morphine administration results in analgesia via agonism at the μ-opioid receptor on the neurons, it is also activates glial cells via TLR-4, resulting in the production of neuroexcitatory mediators.…”
Section: Opioid-induced Glial Activationmentioning
confidence: 99%